The Willow Pattern Plot ORT - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (Oxford university press UK, 1986)
"The Willow Pattern" from the Oxford Reading Tree series is a story that blends adventure and mystery with a touch of history and culture. The plot revolves around a character who learns the story behind a traditional Chinese willow-patterned plate. The story explores the legend depicted on the plate, which involves themes of love, betrayal, and tragedy. In the tale, the main characters uncover the story of a young couple who are deeply in love but face opposition from their families. The lovers' plight unfolds as they try to be together, leading to a dramatic and emotional conclusion. The willow pattern on the plate is used as a way to visually tell the tragic story, connecting the past with the present.
Title Page & Introduction Brief background or teaser about a mysterious adventure. Characters Introduced Biff, Chip, Kipper, Wilf, Wilma, Nadim, and the Magic Key. The Magic Key Adventure Begins The key glows and transports the children into a willow-patterned porcelain world. Setting the Scene Traditional Chinese-style setting with temples, bridges, a palace, and a river. Main Conflict The children meet Koong-se and Chang, lovers in danger due to the angry Mandarin father who forbids their union. Climax The children help Koong-se and Chang escape by outsmarting the Mandarin. Resolution Koong-se and Chang are transformed into doves in the classic willow pattern legend style. The children return home safely, reflecting on the adventure. Moral / Message Loyalty, bravery, and cleverness are celebrated. A nod to understanding and appreciating stories from other cultures.
H3
Build comprehension through complex plot structure. Enhance vocabulary and understanding of story structure (beginning, middle, climax, end). Introduce cultural stories and legends in an engaging format. Encourage inference, prediction, and empathy through character actions and outcomes.
Keywords: Supplementary reading material